Urban and Rural Family Background and Parental Educational Involvement of Primary School Students - MA YUWEI; OOI BOON KEAT (International Journal of Multidisciplinary Research and Studies, 2024)
Based on the reality of significant difference in the academic achievement of urban and rural students in Dujiangyan City, and the analysis of existing literature, this study deduces that the factor behind the difference in the academic achievement of urban and rural students in Dujiangyan City is the significant difference in family factors between urban and rural areas, and proposes the hypothesis that there is a significant difference in the family backgrounds of urban and rural primary school students and in the educational involvement of their parents. In this study, one primary school in each urban and rural area was selected for sampling and 346 valid questionnaire answers were obtained. Cross-tabulation analysis and independent samples t-test for each variable by school showed that there is a significant difference between family background and parental educational involvement of students in urban and rural schools, with students in urban schools being significantly better than students in rural schools. In the demographic data, there were no significant differences in the proportion of students by gender and the proportion of only children, but the proportion of children left behind and the proportion from single-parent families were significantly higher in rural than in urban areas.